Remote Working and Mental Health during the First Wave of COVID-19 Pandemic - Marco Bertoni; Danilo Cavapozzi; Giacomo Pasini; Caterina Pavese (Institute of Labor Economics (IZA), 2021)
We use longitudinal data from the SHARE survey to estimate the causal effect of remote working during the COVID-19 pandemic on mental health of senior Europeans. We face endogeneity concerns both for the probability of being employed during the pandemic and for the choice of different work arrangements conditional on employment. Our research design overcomes these issues by exploiting variation in the technical feasibility of remote working across occupations and in the legal restrictions to in-presence work across sectors. We estimate heterogeneous effects of remote working on mental health: we find negative effects for respondents with children at home and for those living in countries with low restrictions or low excess death rates due to the pandemic. On the other hand, the effect is positive for men and for respondents with no co-residing children.
Keywords: I10; J22; J24; J81; 330; mental health; remote working; COVID-19; SHARE